Maintenance works at SMK Landas / Wan Nor Hakimah Wan Abu Bakar - Wan Abu Bakar, Wan Nor Hakimah (Universiti Teknologi MARA UiTM,Perak, 2022)
This report is prepared to provide readers with detailed about the information on my industrial training at the Hulu Terengganu Public Works Department (JKR). Other than that, the industrial training is one of the compulsory that curriculum at Building Surveyor course that must be completed by students whether practical in consultants, factories and companies. This course is designed to equip students with job experience and information before they begin working in the real world. My industrial training is the Public Works Department or known as JKR which provides maintenance and construction work or the like to the public sector in Malaysia. At the Public Works Department, I was sent to the Building Unit as well as building maintenance. However, in the building unit, there are 3 parts namely Development Project, Maintenance, Electrical Engineer. Throughout my placement, I have learned many new sciences about building maintenance. This knowledge is useful for me in the future and gives me many advantages to prepare myself for future career. Last but not least, when completing industrial training at JKR, this report should be including an introduction, a brief background of this company, tasks and mini-projects that have been assigned to me, recommendations, and conclusions in detail while undergoing industrial training at JKR.